IMPROVING THE QUALITY OF PUBLIC SERVICES IN THE SOCIETY 5.0 ERA THROUGH DIGITAL LITERATURE CAPABILITIES OF LLDIKTI APPARATUS FOR REGION XVI - Halid, Irwan; Hatu, Rauf A. (Public Policy Journal, 2022)
Public services provided by the government must be able to keep pace with and in line with the digital technology that is developing today. The development of digital technology today will facilitate all government actions in providing public services in accordance with the authority and duties provided. The development of digital technology today is made by humans is growing, one of which is Society 5.0. The research method used is case studies, with research data collection techniques using literature studies derived from the documents, reports, books, scientific journals relevant to this study. The analysis technique used is a data analysis technique. The results of the study explain This requires increasing the competence of optimal apparatus to boost the credibility of government agencies by improving the quality of public services based on digital technology. The development of apparatus competence is one of which is the ability of digital literacy skills. The concept of digital leadership is used to develop the vision and mission of digital technology-based public services carried out by leaders in the face of uncertain and complex circumstances. The application of digital technology enables the creation of more efficient public services. The use of digital technology supported by reliable infrastructure and human resources is felt to be able to bridge access to public services amid all the drawbacks owned by the region.